DARI ARENA KE MEMORI: KHAZANAH ARSIP PUSAT PRODUKSI FILM NEGARA SERI SIARAN KHUSUS 1959 - 1978: Array - Dharwis Widya Utama Yacob (Jurnal Kearsipan, 2019)
This article describes how special broadcast series archives of Pusat Produksi Film Negara (PPFN) 1959 – 1978 might be a part of the making of Indonesian sport memory. This series makes us able to understand the memory and to some extent the information about the memory are available and accessible through the making of inventory. The archives themselves are audio-visual ones.